Leandro de Sagastizábal y Alejandra Giuliani, Un editor argentino: Arturo Peña Lillo, Buenos Aires, Eudeba, 2014, 176 páginas. - Blanco, María Julia (2015)
Fil: Blanco, María Julia. Universidad Nacional de Rosario; Argentina.